Sex differences in blackout: evidence of a relationship between disorders of arousal during sleep and alcohol-related blackout in females - Elliott, Grace M.; Vidrascu, Elena; Robertson, Madeline M.; Sheridan, Margaret A.; Robinson, Donita L.; Boettiger, Charlotte A. (Frontiers in Psychology, 2026)
RationaleDisorders of arousal (DoA) constitute a class of related, heritable conditions that includes sleepwalking, sleep terrors, and confusional arousals. These disorders are defined by behavioral features which are shared with a separate phenomenon, alcohol-related blackout (ARB). Both ARB and DoA are characterized by full or partial amnesia and disinhibited behavior with maintenance of nearly normal motor function. While these disorders share phenomenology, to our knowledge no previous studies have examined the relationship between them. This is an important gap in the literature as the existence of a relationship between DoA and ARB would indicate potential shared underlying pathophysiology and genetic risk, possibly opening new pathways for research.ObjectivesThe current study intended to probe the relationship between history of ARB and history of DoA among adults as a first step in determining whether they may be connected by shared neurophysiology, and whether there is a role of sex in that relationship. To control for alcohol intake, we examined whether DoA history interacted with alcohol use to predict ARB likelihood.MethodsA demographically diverse sample (n = 358) of adult (ages 18–72) United States citizens completed an online survey assessing self-reported drinking behaviors, lifetime history of ARB, and lifetime history of DoA episodes via the Munich Parasomnia Screening.ResultsConsistent with the literature, greater levels of past year alcohol misuse predicted higher likelihood of ARB in our sample. A novel finding is that history of DoA episodes also interacted with alcohol use to predict higher likelihood of ARB in females only.ConclusionFemale individuals with a history of DoA may be more susceptible to experiencing ARB than individuals without such a history, suggesting that the two states may share a neurophysiological foundation.